1981
DOI: 10.1007/bf00034267
|View full text |Cite
|
Sign up to set email alerts
|

Effect of temperature on light utilization efficiency of leaves in C3 legumes and C4 grasses

Abstract: The effect of temperatures between 15 and 50°C on the light utilization efficiency of leaf net photosynthesis was studied in two C 4 grasses and two C3 legumes. In the legumes, light utilization efficiency (~ mol of CO2 f'txed per t~ Einstein of incident photosynthetic quantum flux) declined linearly with temperature between 15 and 45 ° C. On the other hand, it was independent of temperature between 15 and 40°C in the grasses, but it declined rapidly between 40 and 50 ° C. Values for grasses were greater than … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

1982
1982
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 9 publications
1
8
0
Order By: Relevance
“…The temperature within the crop canopy at a height of 25 cm was lower when the crop was sown on 10 February (30.6 °C) and 19 February (32.8 °C) than on the other dates of sowing, when it ranged between 33.5 and 36.1 °C. The higher temperature might be the cause of the reduction in capsule production due to increased photorespiration and decreased gas exchange ( Hamid et al 1991) and light utilization efficiency ( Ludlow 1980). For a 0.7 °C rise in temperature at a height of 25 cm, the reduction in the number of capsules was 5.2 and 2.6 %, respectively, for 1993 and 1994 when the crop was sown on 1 March as against 19 February.…”
Section: Resultsmentioning
confidence: 99%
“…The temperature within the crop canopy at a height of 25 cm was lower when the crop was sown on 10 February (30.6 °C) and 19 February (32.8 °C) than on the other dates of sowing, when it ranged between 33.5 and 36.1 °C. The higher temperature might be the cause of the reduction in capsule production due to increased photorespiration and decreased gas exchange ( Hamid et al 1991) and light utilization efficiency ( Ludlow 1980). For a 0.7 °C rise in temperature at a height of 25 cm, the reduction in the number of capsules was 5.2 and 2.6 %, respectively, for 1993 and 1994 when the crop was sown on 1 March as against 19 February.…”
Section: Resultsmentioning
confidence: 99%
“…It has previously been shown that the quantum yield values for Ca monocotyledon species [6], may be different from those reported by Ehleringer and Bj6rkman for Ca dicotyledon species [4]. The fact that Ludlow [6] has reported higher values for the light utilization efficiency in Ca grasses over the entire temperature range from 15 to 45°C, when compared to Ca dicotyledon species, may have an impact on previous simulations [3], and interpretations [10] of the distribution of grasses, which have been based on the studies of Ehleringer and Bj6rkman [4].…”
Section: Resultsmentioning
confidence: 99%
“…The fact that Ludlow [6] has reported higher values for the light utilization efficiency in Ca grasses over the entire temperature range from 15 to 45°C, when compared to Ca dicotyledon species, may have an impact on previous simulations [3], and interpretations [10] of the distribution of grasses, which have been based on the studies of Ehleringer and Bj6rkman [4]. The results of the current study contrast with those of Ludlow [6], in demonstrating that the quantum yield of C4 monocotyledons in normal air (21% 02,340cm a m-3), at 25 to 30°C, is very similar to that of C3 monocots and dicots ( Table 1). The results from the current study are also different from those of Bull [2], in which Ca plants were observed to possess light utilization efficiencies which were higher than those of C3 plants at 25-26°C.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Little variation in the light-utilization efficiency (equivalent to (p-) was found in an analysis of several vegetative crops in the UK (Charles-Edwards, 1978a) or in (/)., for several C3 and C4 species when measured at 25 30 C (Ehleringer & Bjorkman, 1977). However, recent results suggest that some C4 grasses may have higher quantum yields (0,) than certain C3 legumes (Ludlow, 1980). Earlier reports of differences in (f).^ were suggested as confirming, at the physiological level, kinetic differences in the A^,,,(CO2) of the enzyme RUP2 carboxylase/oxygenase between diploid and tetraploid cultivars of L. perenne (Garrett, 1978;Rathnam & Chollet, 1980).…”
Section: Discussionmentioning
confidence: 97%